Template and Temperature-Controlled Polymorph Formation in Squaraine Thin Films - Balzer, Frank (Langmuir : the ACS journal of surfaces and colloids, 2022)
Controlling the polymorph formation in organic semiconductor thin films by the choice of processing parameters is a key factor for targeted device performance. Small molecular semiconductors such as the prototypical anilino squaraine compound with branched butyl chains as terminal functionalization (SQIB) allow both solution and vapor phase deposition methods. SQIB has been considered for various photovoltaic applications mainly as amorphous isotropic thin films due to its broad absorption within the visible to deep-red spectral range. The two known crystalline polymorphs adopting a monoclinic and orthorhombic crystal phase show characteristic Frenkel excitonic spectral signatures of overall H-type and J-type aggregates, respectively, with additional pronounced Davydov splitting. This gives a recognizable polarized optical response of crystalline thin films suitable for identification of the polymorphs. Both phases emerge with a strongly preferred out-of-plane and rather random in-plane orientation in spin-casted thin films depending on subsequent thermal annealing. By contrast, upon vapor deposition on dielectric and conductive substrates, such as silicon dioxide, potassium chloride, graphene, and gold, the polymorph expression depends basically on the choice of growth substrate. The same pronounced out-of-plane orientation is adopted in all crystalline cases, but with a surface templated in-plane alignment in case of crystalline substrates. Strikingly, the amorphous isotropic thin films obtained by vapor deposition cannot be crystallized by thermal postannealing, which is a key feature for the spin-casted thin films, here monitored by polarized in situ microscopy. Combining X-ray diffraction, atomic force microscopy, ellipsometry, and polarized spectro-microscopy, we identify the processing-dependent evolution of the crystal phases, correlating morphology and molecular orientations within the textured SQIB films